UNDERSTANDING TOLERANCE: STUDENT PERCEPTIONS OF ISLAMIC RELIGIOUS EDUCATION IN PUBLIC UNIVERSITIES - Anwar, Saepul; Fakhruddin, Agus; Faqihuddin, Achmad; Sudirman, Sudirman; Romli, Usup (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
This study underscores the importance of teaching moderation in Islamic Religious Education (IRE) lectures at public universities (PU) to foster a climate of tolerance among students, countering radicalism and extremism. The primary objective is to explore student perceptions of tolerance learning within their religious courses. Employing a quantitative approach, the researchers conducted a descriptive survey involving 795 respondents, utilizing a cross-sectional design for data collection via a Likert scale questionnaire. Results revealed that a significant majority of students, 87.82%, hold a very good perception of tolerance learning in IRE lectures. Further analysis indicated that over 90% of respondents viewed the attitudes and thoughts of IRE lecturers on religious moderation positively (97.74%). Similarly, 95.37% appreciated the teaching methods and processes that enhance tolerance learning, while 93.38% positively assessed the teaching materials that promote these values. These findings indicate that tolerance learning is effectively occurring in IRE courses at PU. This research reinforces the strategic role of Islamic Religious Education in internalizing tolerant values among students, ultimately contributing to the promotion of religious moderation within the educational context.